2008
DOI: 10.1080/13506120802005965
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic ameloblast-associated protein nature of the amyloid found in calcifying epithelial odontogenic tumors and unerupted tooth follicles

Abstract: We have previously reported that the amyloid found in three patients with calcifying epithelial odontogenic tumors (CEOT) was composed of N-terminal fragments of a putative 153-residue protein specified by a gene designated FLJ20513 now known to represent exons 5 through 10 of the odontogenic ameloblast-associated protein (ODAM) locus that encodes a 279-residue polypeptide. Confirmation of the amyloidogenic potential of ODAM has resulted from analyses of four other cases where we found, in addition, a 74-resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 13 publications
1
30
1
1
Order By: Relevance
“…Through chemical analyses of amyloid fibrils isolated from three specimens, we found that these components were composed of N-terminal fragments of a 153-residue hypothetical protein specified by the FLJ20513 gene (a short form of ODAM cDNA cloned from the Kato III human signet-ring gastric carcinoma cell line [9,10]), where the last six of ten protein-encoding exons of ODAM are located. Subsequently, in studies of amyloid from four other CEOT cases, we identified varying amounts of a second ODAM-related protein with residues originating from the fourth exon (11). This discovery provided conclusive evidence for the transcription of a longer ODAM product that was predicted to consist of 279 amino acids, 126 of which are products of the first four coding exons (1,4).…”
Section: Introductionmentioning
confidence: 86%
“…Through chemical analyses of amyloid fibrils isolated from three specimens, we found that these components were composed of N-terminal fragments of a 153-residue hypothetical protein specified by the FLJ20513 gene (a short form of ODAM cDNA cloned from the Kato III human signet-ring gastric carcinoma cell line [9,10]), where the last six of ten protein-encoding exons of ODAM are located. Subsequently, in studies of amyloid from four other CEOT cases, we identified varying amounts of a second ODAM-related protein with residues originating from the fourth exon (11). This discovery provided conclusive evidence for the transcription of a longer ODAM product that was predicted to consist of 279 amino acids, 126 of which are products of the first four coding exons (1,4).…”
Section: Introductionmentioning
confidence: 86%
“…Studies reveled that ODAM is strongly expressed in the maturation stage of rat incisor ameloblasts and in the junctional epithelium attached to the enamel of erupted molars, as well as in the late stage of ameloblast lineage cell cultures (27,28). ODAM has been associated with other types of odontogenic tumors, namely calcifying epithelial odontogenic tumors (17,29,30). KCOT-1 cells expressed these tumor-related proteins, further confirming the neoplastic nature of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recent studies have shown that the amyloid associated with CEOTs is composed of N-terminal fragments of the ODAM. 8,12 Therefore, this unique odontogenic amyloid, formerly designated APin, is now termed ODAM. 8 Apart from CEOTs, ODAM is highly expressed by mature ameloblasts and is present in the enamel organ as well as in ameloblastomas.…”
Section: Discussionmentioning
confidence: 99%